High risk mitigation measures in the Artificial Intelligence Regulation - Jarosław Czaja (Communications of International Proceedings, 2024)
The aim of the article is to determine the extent to which the Artificial Intelligence Regulation of March 13, 2024 (Artificial Intelligence Act) limits the risk of using products in which artificial intelligence systems are used. This is important because it has been considered a source of danger (e.g. UN resolution on AI security of March 21, 2024). The issue of an extensive scope of regulations in the process of designing and developing systems to ensure safety is also considered, which includes a number of obligations imposed on a broadly defined group of responsible entities. This act very carefully introduces, in some areas, a number of legal measures to counteract broadly understood product risk. The presented article complements research on the most comprehensive legal act on artificial intelligence in the field of security measures. For this purpose, a literature review was carried out and selected legal acts were analyzed. The research carried out mainly used a comparative method by referring to the literature in relation to some security measures from the AI Act. The analysis of the Regulation shows that the AI ​​Act may be a great legal challenge for entities marketing products using artificial intelligence systems.
Keywords: European Union law; risk; product liability; artificial intelligence; digital goods